PENGENALAN SOFTWARE MANAJEMEN PRODUKSI PEMBANGUNAN KAPAL IKAN TRADISIONAL PADA SERIKAT PEKERJA SEKAWAN GROUP DI LAMONGAN - Irma Rustini; Nurvita Arumsari; Dika Rahayu Widiana; Yugowati Praharsi; Yuning Widiarti (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
Lamongan as one of the districts that produces the largest fish in East Java has population who work as fishermen as well as traditional fishing boat builders. Based on the results of a survey of the Sekawan Group workers union in Kandangsemangkon Village, Paciran District, Lamongan as a partner in this community service activity, one of the obstacles faced by traditional fishing shipyards is the duration of shipbuilding which is longer than the specified duration. This is due to the absence of definite plans and targets in the construction of ships, this has an impact on the delay in the completion time of ship construction. To overcome this problem, training on the introduction of Microsoft project software was given to traditional shipyard workers. Before and after the training the participants were given a pre-test and post-test. The scores from the pre-test and post-test were processed by t-test to see the difference in scores before and after training. Based on the results of the t test, it can be seen that there are differences in test scores before and after training. In addition, the average value after the training also increased compared to before the training. Keywords: Microsoft Project, Sekawan Group Workers Union, Traditional Fishing Boat.